EFFICACY OF ZINC SULFIDE- CHITOSAN NANOPARTICLES AGAINST BACTERIAL DIABETIC WOUND INFECTION - Mustafa H.N.,; I. Al -Ogaidi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed evaluation, Zinc sulfide-chitosan nanoparticles (ZnS-chitosan NPs) as an antibacterial agent. The nanoparticles of Zinc sulfide-chitosan were synthesized using a single-step colloidal process. Different factors were optimized, which included pH, temperature, reaction time, concentrations of chitosan and Zinc chloride .The optimal conditions was achieved at pH 7, temperature 60℃, reaction time 60min, with 0.04 mg/ml of Zinc chloride, 2.5 ml 0.1mg/ml Sodium sulfide   and 0.009 M chitosan. The size of ZnS-chitosan NPs size was tested by using FESEM which were 35nm, surface morphology was done by using AFM. Moreover, X-ray Diffraction (XRD) characterized the crystal structure. While the nature of functional groups present in ZnS-chitosan nanoparticles was determined by Fourier transforms infrared (FT-IR) analysis. The sensitivity of bacterial isolates to antibiotics were tested, the bacteria were more sensitive, resistant, and moderate range to ten antibiotics. Different concentrations (12.5, 25, 50, 100, 200, and 400 μg/ml) of ZnS-chitosan NPs were investigated against multidrug resistance (MDR) Staphylococcus aureus (Gram-positive bacteria) and Acinetobacter baumannii, Pseudomonas aeruginosa (Gram-negative bacteria). The minimum inhibitory concentration of ZnS-chitosan NPs against pathogenic bacteria was 100 μg /ml for Staphylococcus aureus and Acinetobacter baumannii, while 50 μg /ml for  Pseudomonas aeruginosa. Cytotoxicity effects of ZnS-chitosan on normal cell lines (WRL-68) were investigated by MTT assay. The results showed that the ZnS-chitosan nanoparticles no cytotoxic effect on normal cell line.